Crop evapotranspiration and crop coefficient of jatropha from first to fourth year - Lena, Bruno Patias (2016)
The determination of crop coefficient (Kc) with adequate methodology is important to quantify regional water requirement. Jatropha (Jatropha curcas L.) Kc is still unknown and this information will be essential to provide reliable irrigation parameters, as well as for crop zoning. The objective of this study was to determine jatropha actual crop evapotranspiration (ETc) and Kc from 1st to 4th growing year, and correlate Kc with leaf area index (LAI) and cumulative thermal unit (CTU). The experiment was performed from March 2012 to August 2015 at \"Luiz de Queiroz\" College of Agriculture (ESALQ)/University of São Paulo (USP), at Piracicaba city, SP, Brazil. The experiment was divided into center pivot, drip, and rainfed treatments. Two large weighing lysimeters (12 m2 each lysimeter) per treatment were used to determine jatropha ETc (one plant per lysimeter). Reference evapotranspiration (ET0) was determined by Penman-Monteith method from a weather station data situated close to the treatments. Daily Kc was determined for the two irrigated treatments by the ration between ETc and ET0 (Kc=ETc/ET0). LAI was determined using the LAI-2200 plant canopy analyzer, which was previously calibrated for jatropha canopy type. In all growing years, LAI was almost zero at the beginning of vegetative stage, increasing until a maximum during productive stage, and decreasing to zero in the leaf senescence stage. Annual ETc trend during the three growing was very similar, which was explained by the different growing periods and the LAI variation. In the 1st year Kc was 0.47 for both treatments. In the 2nd, 3rd, and 4th years Kc ranged from 0.15 to 1.38 for center pivot treatment and from 0.15 to 1.25 for drip treatment. Kc average in 2nd, 3rd, and 4th years during vegetative and productive growing periods was 0.77, 0.93, and 0.82 for center pivot treatment, respectively, and 0.69, 0.79, and 0.74 for drip treatment, respectively. The relationship between Kc and LAI for the center pivot treatment was adjusted to a logarithmical equation with coefficient of determination (R2) and root mean square error (RMSE) of 0.7643 and 0.334, respectively. For the drip treatment R2 was 0.8443 and 0.2079, respectively. In all three years analyzed, Kc related to CTU by a 3rd degree polynomial equation for both treatments.